1997
DOI: 10.2307/3284361
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antibodies to Neospora caninum in Different Canid Populations

Abstract: A total of 1,554 dogs from 5 countries on 3 continents were tested for antibodies to Neospora caninum using an indirect fluorescent antibody test. In Australia, overall, 42/451 (9%, 95% confidence interval [CI] 6-12%) dogs were seropositive (Melbourne 11/207 [5%, 95% CI 2-9%]; Sydney 18/150 [12%, 95% CI 7-18%]; Perth 13/94 [14%, 95% CI 8-22%]). Antibodies to N. caninum were also detected in dogs in South America (Uruguay [20%, 95% CI 16-24%, n = 414]) and sub-Saharan Africa (Tanzania [22%, 95% CI 12-36%, n = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
3
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 6 publications
4
50
3
4
Order By: Relevance
“…Globally, there were no seroprevalence differences in relation with age, sex or general clinical aspect. The absence of difference between males and females is in agreement with several studies [10,19,38]. However, a higher frequency in females was previously reported [6].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Globally, there were no seroprevalence differences in relation with age, sex or general clinical aspect. The absence of difference between males and females is in agreement with several studies [10,19,38]. However, a higher frequency in females was previously reported [6].…”
Section: Discussionsupporting
confidence: 93%
“…In comparison with other published studies, it appears that these results revealed a very high level of seroprevalence in dogs in Algeria when compared to results from Brazil (14%) [24], Australia (9%), Falklands Islands (0.2%), Kenya (0%) [38], USA and Canada (7%) [22], and Italy (6.4%) [39]. The seroprevalence in Algerian dogs in the present study is similar to the 29% found in another Italian survey [40].…”
Section: Discussioncontrasting
confidence: 42%
“…There is evidence of a relationship between N. caninum infection in dogs and cattle (WOUDA et al, 2000;WOUDA et al, 1999), as well as an increased risk of neosporosis among sheep and goat herds when they are exposed to contact with dogs (ABO-SHEHADA & ABU- HALAWEH, 2010;BARBER et al, 1997). Thus, identification of seropositive animals and seroprevalence data in dog populations is extremely important for control and prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the prevalence of the parasite in wildlife populations. Neospora caninum antibodies have been found in coyotes (Lindsay et al, 1996), dingos (Barber et al, 1997), and red foxes (Barber et al, 1997;Buxton et al, 1997;Simpson et al, 1997), suggesting a role for wild canids in the epidemiology of neosporosis. Dubey et al (1999) found that 162 (41%) of 400 white-tailed deer (Odocoileus virgianus) from northeastern Illinois had agglutinating antibodies to N. caninum.…”
Section: Prevalence Of Agglutinating Antibodies To Neospora Caninum Inmentioning
confidence: 99%